2015
DOI: 10.13057/biodiv/d160219
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a molybdenum-reducing and SDSdegrading Klebsiella oxytoca strain Aft-7 and its bioremediation application in the environment

Abstract: Pollution as a result of anthropogenic activities is a severe global issue. These activities including inappropriate disposal, industrial and prospecting activities and unnecessary use of agricultural chemicals have triggered international initiatives to eliminate these contaminants. In this work we screen the ability of a molybdenum-reducing bacterium isolated from contaminated soil to grow and reduce molybdenum on various detergents. The bacterium was able to grow on SDS as a carbon source although the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 57 publications
2
58
0
Order By: Relevance
“…An aliquot of the soil suspension (0.1 mL) was then spread onto an agar of the following media (pH 6.5) and incubated at room temperature. The composition (w/v) of the media is as follows: yeast extract (0.5%), MgSO 4 •7H 2 O (0.05%), Na 2 MoO 4 •2H 2 O (0.242% or 10 mM), glucose (1%), (NH 4 ) 2 •SO 4 (0.3%), NaCl (0.5%), agar (1.5%), and Na 2 HPO 4 (0.071% or 5 mM) (Masdor et al 2015). After 48 hours of incubation, several white and five blue colonies appeared.…”
Section: Isolation Growth and Maintenance Of Bacteriummentioning
confidence: 99%
See 2 more Smart Citations
“…An aliquot of the soil suspension (0.1 mL) was then spread onto an agar of the following media (pH 6.5) and incubated at room temperature. The composition (w/v) of the media is as follows: yeast extract (0.5%), MgSO 4 •7H 2 O (0.05%), Na 2 MoO 4 •2H 2 O (0.242% or 10 mM), glucose (1%), (NH 4 ) 2 •SO 4 (0.3%), NaCl (0.5%), agar (1.5%), and Na 2 HPO 4 (0.071% or 5 mM) (Masdor et al 2015). After 48 hours of incubation, several white and five blue colonies appeared.…”
Section: Isolation Growth and Maintenance Of Bacteriummentioning
confidence: 99%
“…The first process is catalysed by bacterial genera, such as Desulfovibrio and Desulfotomaculum, which required complete anaerobicity. On the other hand, the second process is catalysed by numerous heterotrophic bacteria from various genera (Shukor et al 2007;Shukor et al 2008a;Rahman et al 2009;Shukor et al 2009a;Yunus et al 2009;Shukor et al 2009b;Shukor et al 2010a;Shukor et al 2010b;Lim et al 2012;Ahmad et al 2013a;Halmi et al 2013;Ibrahim et al 2015;Masdor et al 2015;Nuraini et al 2015). The second process is a more feasible tool as the conversion occurs under facultative anaerobic conditions, and no toxic gas is produced (Ghani et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the toxicity of molybdenum to such as sheep and cows at levels of several parts per million has been reported (Kincaid, 1980). The removal of molybdenum through bioremediation especially bioreduction is potentially the most economical approach in the long term (Lim et al, 2014), and several molybdenum-reducing bacteria have been reported (Shukor and Syed, 2010;Ahmad et al, 2013;Masdor et al, 2015). Heavy metals reduction coupled with xenobiotic degradation has been reported (Chirwa and Wang, 2000;Chung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals reduction coupled with xenobiotic degradation has been reported (Chirwa and Wang, 2000;Chung et al, 2007). For example, two molybdenum-reducing bacteria with the ability to utilize sodium dodecyl sulfate (SDS) as the sole carbon have been isolated Masdor et al, 2015). The use of foreign microbes for bioremediation could cause ecological problems, and thus is not recommended (Walter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%